PENINGKATAN PENGETAHUAN SISWA SMK DI BEKASI UNTUK PENGETAHUAN AKAN PEMBUATAN BETON TEMBUS SEBAGAI UPAYA MENGATASI DEGRADASI LINGKUNGAN MELALUI WEBINAR - Mulyono, Tri; Purnomo, Adhi; Anisah, Anisah (IKIP Siliwangi Bandung, 2020)
AbstractEnvironmental issues using green materials are becoming attractive as an effort to mitigate floods with pervious asphalt, pervious concrete, paving blocks, and plastic grid pavers, allowing surface runoff to seep through the surface to the ground layer and gravel. On the other hand, quality resources will encourage economic development so that people will be more prosperous. Through webinars by providing additional knowledge of vocational students to improve competence in making pervious concrete. The event will be held on Saturday, 12 September 2020 through Webinar with the â€œZoom Cloud Meetingâ€ application. The number of participants who took part in the activities of 5 SMK in Jakarta and Bekasi was 67 participants. The results of the evaluation using the pre-test and post-test question instruments for 61 respondents stated that (1) Introducing to vocational students or vocational graduates about regulations in the construction industry related to the competence of making pervious concrete for local pavement for prospective construction workers as an effort to reduce the impact environmental degradation